Analisis Model Propagasi Bellhop di Choke Point Selat Lombok. - tinus, agus; Pranowo, Widodo S.; Anggara, Purry Djati; Supriyant, Taufiq (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2024)
The Lombok Strait is one of the strategic choke points frequented by heavy maritime traffic, demanding effective maritime security assurance. To ensure thissecurity, careful maritime control and surveillance are necessary, especiallythrough the use of monitoring tools such as SONAR to detect foreign objects passingthrough the Lombok Strait. This research aimed to analyze the characteristics ofunderwater acoustic wave propagation patterns, particularly in the formation ofshadow zones, using the Bellhop method. Simulations of the Bellhop propagationmodel were conducted using the AcTUP v2.2L Toolbox. Temperature and salinitydepth distribution data from January 01st, 2023, to December 31st, 2023 obtained from Marine Copernicus were used in this research,. The calculation of soundpropagation velocity based on the Medwin empirical equation, with a focus onsource depths of 10, 100, 300, and 500 meters. The simulation results indicated thatthe Bellhop propagation model with a frequency of 100 Hz at a source depth of 300meters produced more shadow zones compared to other source depths. Thesefindings have significant implications for understanding the patterns of acousticwave propagation in the Lombok Strait, providing valuable insights for maritimecontrol and surveillance efforts in the region.